Ecodesign na formação de educadoras infantis : criação de brinquedos e materiais lúdico-didáticos - Antunes, Dulcicléia (2012)
This study was developed following the research line: Educative Processes and Languages, from University of Passo Fundo s (UPF) Faculty of Education Master s Degree. It has as theme the green building (the sustainable design) inside an education towards sustainability and consider the reuse of textile materials for building toys and playful didactic materials, with the purpose of being used to support children s learning. This paper is about a qualitative research whose objective was investigating the toys and playful didactic materials that may be built by Pedagogy s students, with the using of textile manufactory s wastes, inside eco-design workshops. Furthermore, the research intended probing the importance of the luddites bases for children and for teacher s formation; comprehending aesthetical education s principles in a perspective for sustainability; researching which toys and playful-didactic materials may be created with the textiles wastes, in order to be used supporting children s education. The role of luddites bases inside initial and continued teachers formation and the importance of toys and plays along children s development and inside aesthetical education were highlighted, whereas they promote kids capacities of creating new meanings for their own learning and the development of their motricity and creativity. This research also focus the education towards sustainability, concerning about the destination of solid residuals and the development of future aware citizenships about environmental questions, hence they will be able to deal with environmental issues as political ones. Thus they are going to become sensible consumers who will avoid the consumerism and, consequently, the wasting. The essay also turns to environmental issues inside the fashion industry, that imply more nature friendly manufacturing processes; the choice for greener raw materials, which do not attack the nature, beyond avoiding the wasting; with it the economical growth is maintained, arising viable future between society and nature. This research was guided by the social and interactional paradigm and built with interviewing basis constructors (preschool) teachers and UPF s students of pedagogy, beyond the eco-design workshops realized with the students whose take part of the group PIBID (Programa Institucional de Bolsas de Iniciação à Docência/Institutional Program of Scholarships for Teaching Initiation). The obtained information was approached by purport s analyze, what resulted in three categories, each one constituted by three subcategories: the luddites bases (playfulness) inside teachers formation the importance of luddites bases (playfulness) inside children s learning; recognizing the luddites bases inside teachers shaping; the room for the toys and the plays -; Aesthetical education: perceptions and sensibilities - teaching through sensory perceptions with toys; the toy inside skills development; educational process spontaneity and creativity -; An education towards sustainability - society s becoming environmentally aware through education; the relation between students of pedagogy and the scholar community; the building of toys and playful didactic materials with wastes.